A Framework for the Integration of the Emotiv EEG System into the NeuCube Spiking Neural Network Environment for Robotics Control - Wang, Jianfei (Auckland University of Technology, 2014)
As BCI has been widely studied in recent years, lots of BCI applications have been de-veloped. In this thesis, to implement BCI into individual devices is simulated by con-trolling a robot. Before discussing the experiment, a literature review is outlined. As the experiment is based on the Emotiv system, a framework of implementing the Emotiv system on NeuCube is stated. The objective is to develop a new feature on NeuCube, which can record EEG data in real-time through the Emotiv headset. The limitations and potential future research areas are highlighted at the end.
Keywords: EEG data; NeuCube; Robot control